Sport Psychology practice in Thailand: Does Buddhist religion and spirituality matter? - Yaoping Liu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Existing literature delineates spirituality and religiosity as positive predictors of subjective well-being; however, within literature, this view is not supported by all studies. This mixed proof is potentially attributable to the lack of emphasisi, within academic or popular circles, of the dynamic relationship between faith,religion and an individual’s subjective well-being.The present research examined the relationship between faith,Buddhist religiosity and subjective well-being. For measurement,they have been operationalized in terms of their positive and negative effects on the balance of individual life across three categories: (religious, non-religious, and uncertain. Spirituality models have been evaluated in the whole study. Data was collected through questionnaires and resulting findings were implemented through the smart PLS software. Faith and religion have been demonstrated as having a positive effect on subjective well-being (except for interrelation), which does not influence a single person's religious or spirituality status. Rather, the faith concept has only been evaluated on spiritual and unpredictable, and religious status has changed the relationship between religion and subjective well-being. The research found that our most significant difference was to show positive satisfaction for religious identity for religionists, not uncertain citizens. The findings and their effects are interpreted in the context of sport psychology, show that Buddhist religion and spirituality shows a partially inverse and partially positive relationship with sports psyhchology practices.